2018
DOI: 10.1111/anu.12655
|View full text |Cite
|
Sign up to set email alerts
|

Partial and total replacement of fishmeal by a blend of animal and plant proteins in diets forSeriola dumerili: Effects on performance and nutrient efficiency

Abstract: A 154‐day trial was performed to assess the use of an alternative protein blend (corn gluten, krill and meat meal) as a substitute for fishmeal in diets for juvenile yellowtail, using four isolipidic (140 g/kg) and isoenergetic diets (24 MJ/kg) with the same digestible protein content (50%). The control diet was FM100, without replacement, and in FM66, FM33 and FM0, fishmeal was replaced at 33 g/kg, 66 g/kg and 100 g/kg, respectively. At the end of the experiment, no differences in growth parameters were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 49 publications
3
15
0
Order By: Relevance
“…All these parameters were measured daily from Monday to Saturday. These parameters are optimal for S. dumerili in the recirculation system and are similar to other Seriola experiments (Jover et al, ; Monge‐Ortiz, Tomás‐Vidal, Gallardo‐Álvarez et al, ; Monge‐Ortiz, Tomás‐Vidal, Rodriguez‐Barreto et al, ).…”
Section: Methodssupporting
confidence: 81%
“…All these parameters were measured daily from Monday to Saturday. These parameters are optimal for S. dumerili in the recirculation system and are similar to other Seriola experiments (Jover et al, ; Monge‐Ortiz, Tomás‐Vidal, Gallardo‐Álvarez et al, ; Monge‐Ortiz, Tomás‐Vidal, Rodriguez‐Barreto et al, ).…”
Section: Methodssupporting
confidence: 81%
“…Replacement of FM with CPP at 20% and 40% did not cause significant difference in growth performance compared with the FM diet, which means a blend of PPI and CGM effects good protein utilization efficiency. This result was in accordance with replacing FM with protein blend in yellowtail ( Seriola dumerili ) (CGM, krill and meat meals) (Monge‐Ortiz et al, ) and rainbow trout ( Oncorhynchus mykiss ) (lupin and pea protein concentrates) (Zhang, Øverland, Sørensen, et al, ). Using blend of SBM and canola meal effectively replaced up to 50% FM, whereas higher inclusion of plant protein mixtures caused inhibition of growth in kuruma shrimp ( Marsupenaeus japonicus ) (Bulbul et al, ).…”
Section: Discussionsupporting
confidence: 70%
“…Compared with single protein source, blending protein sources can balance amino acid profile, reduce price and improve palatability, as well as reduce indigestible carbohydrate, antinutritional and toxic factors (Bulbul, Koshio, Ishikawa, Yokoyama, & Kader, ; de Francesco et al, ). Thus, high FM substitution level could be achieved by mixture of protein sources (Monge‐Ortiz et al, , ). Zhang, Øverland, Xie, et al () found that mixture of lupin and pea protein concentrates can efficiently replace FM for black sea bream.…”
Section: Introductionmentioning
confidence: 99%
“…However, fishmeal production is strongly dependent on the capture of wild fish. Over-exploitation of wild fish stocks has reached its maximum sustainable level [3]. It is expected that 16% of the total fish captured from the natural resources will be used to produce fishmeal by 2030.…”
Section: Introductionmentioning
confidence: 99%